Human 3D nucleus pulposus microtissue model to evaluate the potential of pre-conditioned nasal chondrocytes for the repair of degenerated intervertebral disc - Kasamkattil, Jesil; Gryadunova, Anna; Schmid, Raphael; Gay-Dujak, Max Hans Peter; Dasen, Boris; Hilpert, Morgane; Pelttari, Karoliina; Martin, Ivan; Schären, Stefan; Barbero, Andrea; Krupkova, Olga; Mehrkens, Arne (Frontiers in Bioengineering and Biotechnology, 2023)
Introduction: An in vitro model that appropriately recapitulates the degenerative disc disease (DDD) microenvironment is needed to explore clinically relevant cell-based therapeutic strategies for early-stage DDD. We developed an advanced 3D nucleus pulposus (NP) micro-tissue (µT) model generated with cells isolated from human degenerating NP tissue (Pfirrmann grade: 2-3), which were exposed to hypoxia, low glucose, acidity and low-grade inflammation. This model was then used to test the performance of nasal chondrocytes (NC) suspension or spheroids (NCS) after pre-conditioning with drugs known to exert anti-inflammatory or anabolic activities. Methods: NPµTs were formed by (i) spheroids generated with NP cells (NPS) alone or in combination with (ii) NCS or (iii) NC suspension and cultured in healthy or DDD condition. Anti-inflammatory and anabolic drugs (amiloride, celecoxib, metformin, IL-1Ra, GDF-5) were used for pre-conditioning of NC/NCS. The effects of pre-conditioning were tested in 2D, 3D, and degenerative NPµT model. Histological, biochemical, and gene expression analysis were performed to assess matrix content (glycosaminoglycans, collagen type I&II), production and release of inflammatory/catabolic factors (IL-6, IL-8, MMP-3, MMP-13) and cell viability (cleaved caspase 3). Results: The degenerative NPµT contained less glycosaminoglycans, collagens, and released higher levels of IL-8 compared to the healthy NPµT. In the degenerative NPµT, NCS performed superior compared to NC cell suspension but still showed lower viability. Among the different compounds tested, only IL-1Ra pre-conditioning inhibited the expression of inflammatory/catabolic mediators and promoted glycosaminoglycan accumulation in NC/NCS in DDD microenvironment. In degenerative NPµT model, preconditioning of NCS with IL-1Ra also provided superior anti-inflammatory/catabolic activity compared to non-preconditioned NCS. Conclusion: The degenerative NPµT model is suitable to study the responses of therapeutic cells to microenvironment mimicking early-stage DDD. In particular we showed that NC in spheroidal organization as compared to NC cell suspension exhibited superior regenerative performance and that IL-1Ra pre-conditioning of NCS could further improve their ability to counteract inflammation/catabolism and support new matrix production within harsh DDD microenvironment. Studies in an orthotopic in vivo model are necessary to assess the clinical relevance of our findings in the context of IVD repair.